A simple procedure for preparing chitin oligomers through acetone precipitation after hydrolysis in concentrated hydrochloric acid. (5th November 2015) - Kazami, Nao; Sakaguchi, Masayoshi; Mizutani, Daisuke; Masuda, Tatsuhiko; Wakita, Satoshi; Oyama, Fumitaka; Kawakita, Masao; Sugahara, Yasusato
Highlights: Chitin oligomers are recovered by the use of an acetone precipitation method. This method is highly useful in recovering large chitin oligomers. We compare the hydrolysis reaction of β-chitin with α-chitin. We propose a model during the course of HCl hydrolysis. Abstract: Chitin oligomers are of interest because of their numerous biologically relevant properties. To prepare chitin oligomers containing 4–6 GlcNAc units [(GlcNAc)4–6 ], α- and β-chitin were hydrolyzed with concentrated hydrochloric acid at 40 °C. The reactant was mixed with acetone to recover the acetone-insoluble material, and (GlcNAc)4–6 was efficiently recovered after subsequent water extraction. Composition analysis using gel permeation chromatography and MALDI-TOF mass spectrometry indicated that (GlcNAc)4–6 could be isolated from the acetone-insoluble material with recoveries of approximately 17% and 21% from the starting α-chitin and β-chitin, respectively. The acetone precipitation method is highly useful for recovering chitin oligomers from the acid hydrolysate of chitin. The changes in the molecular size and higher-order structure of chitin during the course of hydrolysis were also analyzed, and a model that explains the process of oligomer accumulation is proposed.